Laporan kajian lapangan di Pulau Borneo: dialek Melayu Sekadau (Jurnal Bahasa, 2022)
This article discusses one of the results of the research fended by Southeast Asian Studies Regional Exchange Program (SEASREP) in Borneo, namely the Sekadau Malay dialect, the lingua franca in the downriver areas of the Sekadau River, an area located about 300 kilometre upriver from the coast near Pontianak, Kalimantan Barat. This dialect is discussed from two perspectives, namely the sociolinguistic and linguistic aspects. From the sociolinguistic aspect, this dialect functions as the first language of the native Malay speakers, the first and second language of the minority migrant groups, the medium of interaction in multiethnic settings in this multilingual society, and the language that serves as the default language for certain pragmatic purposes. In general, many words of the Sekadau Malay dialect are similar to other western Borneo Malay dialects, such as those of Kapuas Hulu, Melawi, Saribas and Sarawak. Phonologically, the Sekadau variant displays phonemic contrast between /kl and/?/, a final glottal stop added to certain words, /hi corresponding to both /hi and 171, and the palatalization of the velar nasal after the high vowel, [i].